STRATEGI PENGEMBANGAN TEKNOLOGI INFORMASI PERPUSTAKAAN PERGURUAN TINGGI DI ERA MILENIUM (Studi Kasus di UPT Perpustakaan Universitas Sebelas Maret) - Bambang Hermanto (Jurnal Pustaka Ilmiah, 2019)
Library library users are included in the millennial generation category that is familiar with information technology. The library manages information sources in developing library information technology with user-based approval. Things that need to be developed in the development of information technology in libraries include: 1)Determining the development strategy 2). Done as a user base, 3). Library readiness and librarians in improving service quality, 4). Implement the results of development, 5) carry out continuous evaluations.Keywords: Library information technology, college library, Millennium Era